Construction of shear wall simple formwork system / Muhammad Izzat Mohamad Rahmat - Mohamad Rahmat, Muhammad Izzat (Universiti Teknologi MARA, Perak, 2022)
Walls are one of the most important structure elements of a building. A wall plays several functions in the performance of a building and these functions need to be fully understood in order to create suitable and comfortable building as well as providing privacy also as protection from weather. This report will discuss about simple formwork system for the load bearing wall (shear wall) of the building. This report was conducted for The Construction of public residential development consist of two blocks apartment 16 storey and 17 storey (463 units), 3 storey multilevel car park and common facilities block on PT 4284 (Zone 7C) and upgrading works at part of green area and buffer zone, Precinct 11, Putrajaya owned by Putrajaya Holdings. The objective of this report is to investigate the construction of shear wall and the way how it carried out. It will focus on the whole process shear wall construction using the simple formwork system. It also investigates the equipment and machinery in the methods simple formwork system for shear wall construction and to determine the time that have been used for the construction. This report will also look to at the problem and the solution in wall construction that would fulfill the criteria of shear wall. The methods that were used in order to gain information about the objective discussed were through observation, interviewing staff and document review. To conclude, the identification of shear wall construction method, machineries and tools, the time used for the shear wall construction and problem and solution during shear wall construction had been achieved effectively.